Legal Awareness about Women Rights: The Indian Adolescent - SOHAL, MS. PUNEET; BHATIA, DR. RANJANA; SHARMA, DR. SARITA (The journal of contemporary issues in business and government, 2021)
With the changing norms and evolving society, it becomes significant for the youth to be aware and informed about the benefits their country’s laws provide them through their set rights and duties. The laws for women in any country help in succoring them towards their well- being and development in both personal and professional roles. This research aimed at evaluating and identifying the level of legal awareness the adolescents of the national capital region of India had about these very laws made for women safety, security and progress.